2006
DOI: 10.1191/0959683606hl970rr
|View full text |Cite
|
Sign up to set email alerts
|

Sclerochronological records of Arctica islandica from the inner German Bight

Abstract: Sclerochronological records of interannual shell growth variability were established for eight modern shells (26 to 163 years of age) of the bivalve Arctica islandica, which were sampled at one site in the inner German Bight. The records indicate generally low synchrony between individuals. Spectral analysis of the whole 163-yr masterchronology indicated a cyclic pattern with a period of 5 and 7 years. The masterchronology correlated poorly to time series of environmental parameters over the last 90 years. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…We can confirm the extraordinary high ages attained in populations around Iceland, where animals close to 200 y old are regularly encountered (Scho¨ne et al 2004, Scho¨ne et al 2005a, Strahl et al 2007). In the southern North Sea, maximum age appears to be about 150 y (Witbaard et al 1994, Witbaard et al 1999, Epple et al 2006, and our value of 125 y for the German Bight fits well in this picture. No information on age of A. islandica form the Norwegian coast or Kattegat has been available so far, but our estimate for the A. islandica individual lifetime energy budget parameters.…”
Section: Growth and Longevity Of A Islandicasupporting
confidence: 81%
See 1 more Smart Citation
“…We can confirm the extraordinary high ages attained in populations around Iceland, where animals close to 200 y old are regularly encountered (Scho¨ne et al 2004, Scho¨ne et al 2005a, Strahl et al 2007). In the southern North Sea, maximum age appears to be about 150 y (Witbaard et al 1994, Witbaard et al 1999, Epple et al 2006, and our value of 125 y for the German Bight fits well in this picture. No information on age of A. islandica form the Norwegian coast or Kattegat has been available so far, but our estimate for the A. islandica individual lifetime energy budget parameters.…”
Section: Growth and Longevity Of A Islandicasupporting
confidence: 81%
“…A. islandica is a long-lived bivalve species with a maximum age ranging from 40 y in the Baltic Sea (Zettler et al 2001, Begum et al 2009) to ;400 y off Iceland (Scho¨ne et al 2005b; see also Thompson et al 1980b). A. islandica is a suitable archive of past environmental conditions that can be reconstructed from morphological and biogeochemical properties of the shell (e.g., Epple et al 2006, Scho¨ne et al 2005b. Its wide geographical range of occurrence combined with its longevity makes A. islandica a prime candidate for monitoring and modeling long-term environmental and ecological dynamics (Harding et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Growth synchrony among G. pilosa individuals indicates that some aspect of the environment influences growth, though relationships between shell growth and external factors can be complex, especially in shallow coastal environment with highly variable conditions (Eppl e et al, 2006). Previous sclerochronological studies have identified temperature as one of the main drivers of shell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recorded MLSPs (MLSP rec ) of A. islandica differ regionally between populations from sub-Arctic environments around Iceland (IC) with individual ages of more than 350years (Schöne et al, 2005;Wanamaker et al, 2008), and from the German Bight (GB) with recorded individual MLSPs of 150years (Witbaard and Klein, 1994;Witbaard et al, 1999;Epplé et al, 2006). Low salinity populations with conspicuously shorter life expectancies have established in brackish waters of the sub-Arctic White Sea with a MLSP rec of 53years and the temperate Baltic Sea with MLSP rec of 40years (Begum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%